Liver disease and the renin–angiotensin system: Recent discoveries and clinical implications - Lubel, John S (J Gastroenterol Hepatol, 2008)
The renin–angiotensin system (RAS) is a key regulator of vascular resistance, sodium and water homeostasis and the response to tissue injury. Historically, angiotensin II (Ang II) was thought to be the primary effector peptide of this system. Ang II is produced predominantly by the effect of angiotensin converting enzyme (ACE) on angiotensin I (Ang I). Ang II acts mainly through the angiotensin II type‐1 receptor (AT(1)) and, together with ACE, these components represent the ‘classical’ axis of the RAS. Drug therapies targeting the RAS by inhibiting Ang II formation (ACE inhibitors) or binding to its receptor (angiotensin receptor blockers) are now in widespread clinical use and have been shown to reduce tissue injury and fibrosis in cardiac and renal disease independently of their effects on blood pressure. In 2000, two groups using different methodologies identified a homolog of ACE, called ACE2, which cleaves Ang II to form the biologically active heptapeptide, Ang‐(1–7). Conceptually, ACE2, Ang‐(1–7), and its putative receptor, the mas receptor represent an ‘alternative’ axis of the RAS capable of opposing the often deleterious actions of Ang II. Interestingly, ACE inhibitors and angiotensin receptor blockers increase Ang‐(1–7) production and it has been proposed that some of the beneficial effects of these drugs are mediated through upregulation of Ang‐(1–7) rather than inhibition of Ang II production or receptor binding. The present review focuses on the novel components and pathways of the RAS with particular reference to their potential contribution towards the pathophysiology of liver disease.